2018
DOI: 10.1111/cas.13647
|View full text |Cite|
|
Sign up to set email alerts
|

Long non‐coding RNA NEAT1 promoted ovarian cancer cells’ metastasis through regulation of miR‐382‐3p/ROCK1 axial

Abstract: Long non‐coding RNA (lncRNA) are extensively involved in various malignant tumors, including ovarian cancer (OC). In the present study, we focused on the expression and function of nuclear enriched abundant transcript 1 (NEAT1) in OC cells’ metastasis. We demonstrated that NEAT1 was upregulated in OC tissue specimens and cell lines. In addition, we revealed that depression of NEAT1 inhibited OC cells’ metastasis and the expression of Rho associated coiled‐coil containing protein kinase 1 (ROCK1), which is a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…Emerging studies have validated that numerous lncRNA are aberrantly expressed in EOC and play crucial roles in tumorigenesis and progression . For instance, the expression of the lncRNA human ovarian cancer‐specific transcript 2 (HOST2) was found to be upregulated in EOC tissue, promoting cell proliferation and metastasis by sponging miRNA let‐7b .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging studies have validated that numerous lncRNA are aberrantly expressed in EOC and play crucial roles in tumorigenesis and progression . For instance, the expression of the lncRNA human ovarian cancer‐specific transcript 2 (HOST2) was found to be upregulated in EOC tissue, promoting cell proliferation and metastasis by sponging miRNA let‐7b .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have validated that numerous lncRNA are aberrantly expressed in EOC and play crucial roles in tumorigenesis and progression. 15,16 For instance, the expression of the lncRNA human ovarian cancer-specific transcript 2 (HOST2) was found to be upregulated in EOC tissue, promoting cell proliferation and metastasis by sponging miRNA let-7b. 17 In addition, highly expressed homeobox (HOX) transcript antisense intergenic RNA (HOTAIR) was found to be closely related to poor EOC prognosis and the promotion of EOC migration and invasion through matrix metalloproteinases (MMP) and epithelial-mesenchymal transition (EMT) in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Several researches have been said that ROCK1/F-actin pathways contributed to the mitochondrial related cell apoptosis, migration inhibition, and proliferation arrest in several cancer cells. 36,37 Thus, a question was raised whether miR-31 functions in HepG2 cells through ROCK1/F-actin pathways. To answer it, Y-27632, the inhibitor of ROCK1, was used in HepG2 cells transfected with miR-31 mimic.…”
Section: Mir-31 Activates Hepg2 Cell Injury Via Rock1/f-actin Pathwaysmentioning
confidence: 99%
“…The nuclear paraspeckle assembly transcript 1 (NEAT1) was a newly identified lncRNA that regulated gene expression by retaining mRNAs for editing in the nucleus (Clemson et al, ). It was reported as an oncogene in several types of human cancers, including hepatocellular carcinoma, lung cancer, oesophageal cancer, colorectal cancer, renal cell carcinoma, ovarian cancer, breast cancer, and glioma (F. Liu et al, ; Y. Liu, Wang, Fu, & Lu, ; Yu, Li, Zheng, Chan, & Wu, ; Zhou et al, ). However, the role of NEAT1 in RB remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that NEAT1 was elevated in multiple cancers, and it acted as an oncogene in these cancers (F. Liu et al, 2017;Y. Liu et al, 2018;Yu et al, 2017).…”
mentioning
confidence: 99%